PENGARUH MODEL PEMBELAJARAN RESITASI DALAM PEMBELAJARAN MENULIS TEKS ULASAN SISWA KELAS VIII SMPN 32 PALEMBANG - Triana, Yola; Agustina, Juaidah; Murniviyanti, Liza (Universitas PGRI Palembang, 2023)
This research was motivated by students of class VIII at SMP Nelgelri 32 Palembang who had many obstacles in the learning process of writing texts, one of which was the lack of students' understanding of the material taught by Gulrul. Seeing the conditions of self-learning, it is necessary to have an action to implement a learning model that is expected to generate ideals or ideas in writing review texts in Indonesian subjects. One of the models that is often used in learning in schools is the telorbult learning model, which is the recitation model. This type of research is quantitative research, with a correlation approach. This research aims to find out whether there is an effect of the recitation learning model in writing text lessons for class VIII students of SMP Nelgelri 32 Palelmbang. The population in this research amounted to 209 students, and the research sample consisted of 60 students who were divided into 34 students in class VIII.3 as an experimental class and 35 students in class VIII.4 as a control class. How to collect data through questionnaires and documentation. Based on the results of data processing and data analysis which was carried out using the SPSS 22 program, it was concluded that the hypothetical influence of the recitation learning model in the learning of text writing for grade VIII students of SMPN 32 Palelmbang. The greater the effect is 0.763 or 76.3% which is in the range 0.60-0.799 with the toadstool category, while the other 23.7% is affected by other factors. Meanwhile, the relational level of the recitation learning model to the writing skills of review text was 0.823 or 82.3%, which was in the range of 0.80-1.000 with a very strong category. This means that there is a very strong relationship between the recitation learning model and the text writing skills of students of SMPN 32 Palelmbang during the entire 2022/2023 academic year. Keywords: Recitation Learning Model, Text Writing Skills Review